2017
DOI: 10.1186/s40621-017-0108-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and ethnic/racial disparities in the distribution of pediatric injuries in South Florida: implications for the development of community prevention programs

Abstract: BackgroundThe state of Florida continues to report significant gender, ethnic and racial disparities in trauma incidence, access to care and outcomes in the adult population. Our objective was to assess pediatric injury profiles and ethnic/racial disparities of specific injuries in a Regional Trauma Center (TC) in South Florida.MethodsRetrospective data from November 2011 to December 2015 were obtained from the Level 2 TC registry for children ≤21 years old. Demographic, injury pattern, geographic area, injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…We found that 27 of the 32 studies (84.4%) [ 16 , 24 , 25 , 28 31 , 34 , 35 , 37 54 ] were published after 2010, indicating that geographic factors influencing major trauma have recently become a priority for study. Of the 32 studies, 18 studies [ 16 , 24 , 25 , 27 , 29 , 30 , 32 , 39 – 43 , 45 , 47 50 , 52 ] selected study subjects of all ages, eight studies [ 26 , 34 , 35 , 38 , 44 , 46 , 51 , 53 ] were adults, one [ 54 ] studied people in their 50s or older, and five [ 28 , 31 , 33 , 36 , 37 ] studied children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…We found that 27 of the 32 studies (84.4%) [ 16 , 24 , 25 , 28 31 , 34 , 35 , 37 54 ] were published after 2010, indicating that geographic factors influencing major trauma have recently become a priority for study. Of the 32 studies, 18 studies [ 16 , 24 , 25 , 27 , 29 , 30 , 32 , 39 – 43 , 45 , 47 50 , 52 ] selected study subjects of all ages, eight studies [ 26 , 34 , 35 , 38 , 44 , 46 , 51 , 53 ] were adults, one [ 54 ] studied people in their 50s or older, and five [ 28 , 31 , 33 , 36 , 37 ] studied children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…A past study reported that whites and African Americans had similar injury-related ED visit rates, although African Americans had more overall visits to the ED 31 . Another study, in a single center, found that Hispanics and whites had a higher relative risk of falls than African Americans 32 . No clear conclusions can be drawn about the effects of race on fall injuries from our statewide data; however, additional analysis is underway to investigate the disparities associated with race/ethnicity and falls geographically.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that about 40 per cent of deaths due to unintentional injuries are actually preventable. 2 Examples of unintentional injuries are events such as motor vehicle accidents, burns, prescription drug overdoses, and falls in the elderly population. Because of the unintentional and preventable nature of many traumatic injuries, trauma centers are required to implement prevention programs that have a vital role in educating the community on preventable injuries.…”
mentioning
confidence: 99%
“…Mapping the different types of injuries across population areas serves as an indicator of what type of prevention programs are needed. Irizarry et al (2017) analyzed ethnic/racial disparities in the patterns of injury in a south Florida trauma center. Drawing on the data from their trauma registry, they analyzed demographics, injury patterns, geographic area, injury scores, and outcome data.…”
mentioning
confidence: 99%
See 1 more Smart Citation